2009
DOI: 10.1017/s146114570999099x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of 5-HT1A-mediated neurotransmission in dorsal periaqueductal grey matter accounts for the panicolytic-like effect of chronic fluoxetine

Abstract: Chronic administration of antidepressants such as fluoxetine and imipramine increases the responsiveness of 5-HT(1A) receptors in dorsal periaqueductal grey matter (DPAG), a midbrain area consistently implicated in the pathogenesis of panic disorder. This effect has been related to the clinically relevant anti-panic action of these drugs. In this study we determined whether long-term administration of fluoxetine also affects 5-HT efflux in DPAG. As a comparison, the effect of chronic treatment with the anxioly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 57 publications
1
16
1
8
Order By: Relevance
“…Importantly, our data revealed that at this time point of treatment (3 days), imipramine, clomipramine or desipramine impaired escape expression in the elevated T-maze, suggesting a panicolytic-like effect. This behavioral effect was not seen after 3-day administration of fluoxetine, which is reported to inhibit escape after 3-weeks of treatment (Poltronieri et al, 2003;Zanoveli et al, 2010). Therefore, in all cases reported above, there is a full temporal concordance between changes in DPAG BDNF levels and the observation of panicolytic-like effects of these ADs in the elevated T-maze.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Importantly, our data revealed that at this time point of treatment (3 days), imipramine, clomipramine or desipramine impaired escape expression in the elevated T-maze, suggesting a panicolytic-like effect. This behavioral effect was not seen after 3-day administration of fluoxetine, which is reported to inhibit escape after 3-weeks of treatment (Poltronieri et al, 2003;Zanoveli et al, 2010). Therefore, in all cases reported above, there is a full temporal concordance between changes in DPAG BDNF levels and the observation of panicolytic-like effects of these ADs in the elevated T-maze.…”
Section: Discussionmentioning
confidence: 77%
“…Although not specific to GABA, activation of the MAPK pathway may in turn promote the phosphorylation of synapsin I, thus leading to facilitation in synaptic vesicle fusion and neurotransmitter release (Jovanovic et al, 2000). An important consideration in the present paper is that a wealth of evidence shows that after 21-day, but not 3-day treatment, imipramine and fluoxetine also facilitate 5-HT neurotransmission in the DPAG (de Bortoli et al, 2006;Zanoveli et al, 2005Zanoveli et al, , 2007Zanoveli et al, , 2010. For instance, these drugs enhance the anti-escape effect caused by intra-DPAG injection of 5-HT1A-and 5-HT2A-receptor agonists.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Intra-DPAG injections of 5-HT 1A and 5-HT 2A receptor agonists (de Bortoli et al, 2008;de Bortoli et al, 2006;Jacob et al, 2002;Zanoveli et al, 2005;Zanoveli et al, 2007), but not 5-HT 2C receptor agonists (Yamashita et al, 2011), inhibit escape behaviors, either following electrical stimulation of the DPAG, or as assessed in intact, unstimulated, rats exposed to the elevated T-maze. Intra-DPAG injections of 5-HT 1A and 5-HT 2A receptor antagonists in the absence of electrical stimulation of the DPAG have no effect on escape behaviors (de Paula Soares and Zangrossi, Jr., 2004;Nogueira and Graeff, 1995;Yamashita et al, 2011;Zanoveli et al, 2010), suggesting that there is little or no tonic serotonergic influence on DPAG-mediated escape behaviors. All of these studies were conducted in the elevated T-maze.…”
Section: A Putative Panic Inhibition System Involving the Amygdalamentioning
confidence: 97%
“…In addition to enhanced sensitivity of 5-HT 1A and 5-HT 2A receptors in the DPAG following chronic treatment with fluoxetine, chronic treatment with fluoxetine, but not buspirone, increases serotonin release in the DPAG and inhibits escape-like behaviors in the elevated T-maze, an anxiolytic behavioral effect that is prevented by intra-DPAG microinjection of the 5-HT 1A receptor antagonist, WAY-100635 (Zanoveli et al, 2010). Together, these data suggest that both increased serotonin release within the DPAG and increased sensitivity of 5-HT 1A and 5-HT 2A receptors in the DPAG contribute to the anti-panic effects of chronic antidepressant treatment.…”
Section: A Putative Panic Inhibition System Involving the Amygdalamentioning
confidence: 99%